2010
DOI: 10.1080/10803548.2010.11076825
|View full text |Cite
|
Sign up to set email alerts
|

Subjective Health Complaints of Teachers From Primary and Secondary Schools in Hong Kong

Abstract: This study aimed to investigate the subjective health complaints (SHC) teachers subjective health complaints occupational diseases

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

23
113
4
19

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(159 citation statements)
references
References 23 publications
(48 reference statements)
23
113
4
19
Order By: Relevance
“…In the past 12 months, 48% of the teachers presented musculoskeletal symptoms (Table 2). Our findings corroborate with other research on basic education teachers, which showed high prevalence of musculoskeletal symptoms in teachers, ranging from 40% to 95% [18][19][20][21][22][23] . The parts of the body most affected by musculoskeletal symptoms were the knees, ankles and/or feet, neck, wrists/ hands and back (Table 2).…”
Section: Discussionsupporting
confidence: 82%
“…In the past 12 months, 48% of the teachers presented musculoskeletal symptoms (Table 2). Our findings corroborate with other research on basic education teachers, which showed high prevalence of musculoskeletal symptoms in teachers, ranging from 40% to 95% [18][19][20][21][22][23] . The parts of the body most affected by musculoskeletal symptoms were the knees, ankles and/or feet, neck, wrists/ hands and back (Table 2).…”
Section: Discussionsupporting
confidence: 82%
“…Furthermore, overweight is assumed to cause pain by increasing the mechanical stress on the weight-bearing joints. [5] Chronic pain is associated with the prevalence of MSDs where a study conducted in Thailand by Pornnapa Suggaravetsirib shown that chronic disease had significantly 1.6 times higher risk for developing MSD compared to without chronic disease. [16] Table 4 shows the association of the length of employment with musculoskeletal pain could be interpreted as the effect of aging or a cumulative effect of workloads on the musculoskeletal system of the workers.…”
Section: Discussionmentioning
confidence: 99%
“…These may cause teachers to suffer from adverse mental and physical health issues due to a variety of job functions. [5] Nursery school teacher, however, also performs a wide variety of tasks combining basic health, childcare, and teaching duties and those that require sustained mechanical load and constant trunk flexion. [7] Sometimes, teaching is carried out under unfavorable circumstances; in which teacher mobilize their physical, cognitive, and emotional capacity to reach the teaching productive objectives, overdemanding, or generating over the effort of their psychophysiological functions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations